2022
DOI: 10.1681/asn.2021101312
|View full text |Cite
|
Sign up to set email alerts
|

A Founder Mutation in EHD1 Presents with Tubular Proteinuria and Deafness

Abstract: BackgroundThe endocytic reabsorption of proteins in the proximal tubule requires a complex machinery and defects can lead to tubular proteinuria. The precise mechanisms of endocytosis and processing of receptors and cargo are incompletely understood. EHD1 belongs to a family of proteins presumably involved in the scission of intracellular vesicles and in ciliogenesis. However, the relevance of EHD1 in human tissues, in particular in the kidney, was unknown.MethodsGenetic techniques were used in patients with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…8,32 Indeed, the observed redistribution of NHE3 to intracellular compartments observed in ClC-5 KO mice and OK cells was previously attributed to reduced exocytosis or recycling. 6,36 Similarly, endocytic recycling has been implicated as the cause of tubular proteinuria in patients with mutations in EHD1 37 and may also underlie the reduced uptake of filtered proteins in Lowe syndrome. 38,39 Instead, we find that the rate of endosome maturation profoundly affects the efficiency of apical endocytic traffic in PT cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,32 Indeed, the observed redistribution of NHE3 to intracellular compartments observed in ClC-5 KO mice and OK cells was previously attributed to reduced exocytosis or recycling. 6,36 Similarly, endocytic recycling has been implicated as the cause of tubular proteinuria in patients with mutations in EHD1 37 and may also underlie the reduced uptake of filtered proteins in Lowe syndrome. 38,39 Instead, we find that the rate of endosome maturation profoundly affects the efficiency of apical endocytic traffic in PT cells.…”
Section: Discussionmentioning
confidence: 99%
“…A role in caveolar uptake is unlikely considering the caveolin proteins are not expressed in the proximal tubule in vivo ( Zhuang et al, 2011 ), consistent with a more likely role for Pacsin2 in clathrin-dependent endocytosis. Of note, a recent study has shown that mutation of the PACSIN2 binding partner EHD1, which is involved in endocytic recycling ( Naslavsky and Caplan, 2011 ), causes a rare tubular disorder characterised by low molecular weight proteinuria due to defective endocytic traffic ( Issler et al, 2022 ). Thus, it remains possible that Pacsin2 contributes to both endocytic uptake and recycling within the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified a homozygous missense mutation in the gene encoding the EHD1 protein in patients with low-molecular-weight proteinuria (0.7–2.1 g/d) and high-frequency hearing loss ( Issler et al, 2022 ). To gain further insights into the pathophysiology of the mutant EHD1 protein, we established a knockin mouse model carrying the respective mutation (p.R398W) in the mouse Ehd1 gene.…”
Section: Introductionmentioning
confidence: 99%